Locally isolated Trichoderma harzianum species have broad spectrum biocontrol activities against the wood rot fungal species through both volatile inhibition and mycoparasitism - Chan, Mu En (2023)
Pathogenic root/wood rot fungal species infect multiple urban tree species in Singapore. There is a need for sustainable and environmentally friendly mitigation. We report the local Trichoderma strains as potential biocontrol agents (BCAs) for pathogenic wood rot fungal species such as Phellinus noxius, Rigidoporus microporus, and Fulvifomes siamensis. Isolated Trichoderma strains were DNA-barcoded for their molecular identities and assessed for their potential as a BCA by their rate of growth in culture and effectiveness in inhibiting the pathogenic fungi in in vitro dual culture assays. Trichoderma harzianum strain CE92 was the most effective in inhibiting the growth of the pathogenic fungi tested. Preliminary results suggested both volatile organic compound (VOC) production and direct hyphal contact contributed to inhibition. SPME GC-MS identified known fungal inhibitory volatiles. Trichoderma harzianum strain CE92 hyphae were found to coil around Phellinus noxius and Lasiodiplodia theobromae upon contact in vitro and were possibly a part of the mycoparasitism. In summary, the work provides insight into Trichoderma inhibition of pathogenic fungi and identifies local strains with good potential for broad-spectrum BCAs against root/wood rot fungi in Singapore.